Synthetic Enzyme Engineering In Silico and In Vivo Approaches for Applications in the Halal Food Industry - Anggraini, Welly (Jurnal Pijar Mipa, 2025)
Recent developments in biotechnology and bioinformatics have opened new possibilities for designing enzymes for the halal food sector. This study employs an integrated framework combining in silico modelling and in vivo validation to create synthetic enzymes that are both effective and compliant with halal standards. Computational analyses were conducted to predict enzyme–substrate interactions and evaluate structural stability, while experimental validation confirmed enzymatic activity, thermal stability, and safety profiles. The results demonstrate that this dual approach improves design efficiency, enhances catalytic performance, and ensures enzymes originate from halal-certified sources, addressing a notable gap in current research where optimization and religious compliance are often addressed separately. This methodology bridges molecular biochemistry with Islamic jurisprudence, providing a scientifically grounded approach for producing bioenzymes suitable for industrial applications. By showing that halal verification can be integrated without compromising enzyme functionality, the study provides a model for ethical and religiously responsible food production. The findings have broad implications for the halal food industry, supporting scalable enzyme manufacturing and laying the groundwork for future research in synthetic biology, regulatory compliance, and the development of innovative functional foods.